Pengaruh Penggunaan Metode Baca Iqro terhadap Peningkatan Pemahaman Ilmu Tajwid Santri Putri Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Pelajaran 2024/2025: Penelitian - Lusiawati; Muhammad Yasin; Miftahul Anwar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to determine whether the Iqro reading method influences the improvement of tajwid knowledge among female students at Pondok Pesantren Hidayatul Mubtadiin Jati Agung, South Lampung, in the 2024/2025 academic year, as well as to measure the extent of its influence. This research employs a quantitative method with a one-group pretest-posttest design. The instruments used in the study include questionnaires and cognitive tests in the form of multiple-choice and essay questions. The data analysis techniques involve prerequisite tests, including normality and linearity tests, as well as hypothesis testing using simple linear regression analysis. Based on the results of the study, it can be concluded that the implementation of the Iqro reading method significantly influences the improvement of tajwid understanding among female students at Pondok Pesantren Hidayatul Mubtadiin Jati Agung, South Lampung, in the 2024/2025 academic year. This is evidenced by the increase in students' learning outcomes after being taught using the Iqro method, where all students showed post-test scores above 70. The results of the simple linear regression analysis also show a strong level of significance, with an R Square value of 63.1%. The Iqro method, delivered in a gradual, systematic, and interactive manner, enables students not only to understand tajwid theoretically but also to apply it practically in reading the Qur'an. Question-and-answer activities, reading assessments by the ustadzah, and the habit of identifying tajwid rules before reading make the learning process more meaningful and have a real impact on improving students' abilities. Therefore, the Iqro reading method can be considered an effective alternative for enhancing tajwid understanding in Qur'anic learning within Islamic boarding schools.